The Evolution of Dysfunction - Diener, Paul (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1982)
Cultural ecological theory has typically assumed that evolutionary processes lead inevitably to the emergence of positive functions and useful adaptations (Vayda, Harris, Durham, Barkow, Adams). But biologists are aware that dysfunctions, as well as positive functions, may result from evolution. In both biology and anthropology, dialectical models are better able to incorporate dysfunctional evolutionary trends. In this paper, a “thought experiment” illustrating dysfunctional evolutionary processes is provided. The strengths, and weaknesses, of using biological ideas as “creative analogies” for cultural processes are discussed. We need to pay more attention to the evolution of dysfunctions and to the emergence of contradictions in cultural systems.